Qingzhuan dark tea Theabrownin alleviates hippocampal injury in HFD-induced obese mice through the MARK4/NLRP3 pathway - Yining Lei; Yong Chen; Shuo Zhang; Wei Wang; Min Zheng; Ruyi Zhang (Heliyon, 2024)
Background: Feeding on a high-fat diet (HFD) results in obesity and chronic inflammation, which may have long-term effects on neuroinflammation and hippocampal injury. Theabrownin, a biologically active compound derived from the microbial fermentation of Qingzhuan dark tea, exhibits anti-inflammatory properties and lipid-lowering effects. Nevertheless, its potential in neuroprotection has yet to be investigated. Consequently, this study aims to investigate the neuroprotective effects of Theabrownin extracted from Qingzhuan dark tea, as well as its potential therapeutic mechanisms. Methods: Male C57 mice were subjected to an 8-week HFD to induce obesity, followed by oral administration of Theabrownin from Qingzhuan dark tea. Lipid levels were detected by Elisa kit, hippocampal morphological damage was evaluated by HE and Nissl staining, and the expression levels of GFAP, IBA1, NLRP3, MARK4, and BAX in the hippocampus were detected by immunofluorescence (IF), and protein expression levels of NLRP3, MARK4, PSD95, SYN1, SYP, and Bcl-2 were detected by Western Blot (WB). Results: Theabrownin treatment from Qingzhuan dark tea prevents alterations in body weight and lipid levels in HFD-fed mice. Furthermore, Theabrownin decreased hippocampal morphological damage and reduced the activation of astrocytes and microglia in HFD-fed mice. Moreover, Theabrownin decreased the expression of MARK4 and NLRP3 in HFD-fed mice. Besides, Theabrownin elevated the expression of PSD95, SYN1, and SYP in HFD-fed obese mice. Finally, Theabrownin prevented neuronal apoptosis, reduced the expression of BAX, and increased the expression of Bcl-2 in HFD-fed obese mice. Conclusions: In summary, our current study presents the first demonstration of the effective protective effect of Theabrownin from Qingzhuan dark tea against HFD-induced hippocampal damage in obese mice. This protection may result from the regulation of the MARK4/NLRP3 signaling pathway, subsequently inhibiting neuroinflammation, synaptic plasticity, and neuronal apoptosis.